(untitled) (Research, Society and Development, 2020)
Objective: To investigate the relationship between the condition of being a person with schizophrenia and self-esteem. Method: This is a cross-sectional study, with a quantitative approach, carried out with 12 people with schizophrenia, working in a Psychosocial Care Center in a city in the center-west of the state of São Paulo. Data collection took place from December 2018 to February 2019, using a semi-structured instrument, developed by the authors and applying the Rosenberg Self-Esteem Scale. The data were analyzed using the ANOVA 1 factor, Pearson’s Chi-square test and Fisher’s exact test. The research project was approved by the Research Ethics Committee. Results: The general level of self-esteem was 26.42, with minimum and maximum scores of 23 and 29, and standard deviation of 1.676. It was observed that there is no statistically significant difference between the means of the groups. When classified by categories (low self-esteem, regular self-esteem and high self-esteem), there were no people classified as high self-esteem. For the variables presence of children, existence of a family member with schizophrenia, existence of another mental disorder and use of alcohol, tobacco and other substances, similar behavior was observed (p = 1,000). Final considerations: Self-esteem is directly related to a process of stigmatization. The individual with a mental disorder creates a vicious cycle of social exclusion and discrimination, constituting an enormous barrier to the quality of life.